Low Prevalence of Gastrointestinal Colonization with Antimicrobial-Resistant Bacteria in High Risk Units in a Canadian Tertiary Care Centre. (1996) - Embil, John M; Kabani, Amin; Zhanel, George; Nicolle, Lindsay E
Abstract : OBJECTIVE: To determine the prevalence of antimicrobial-resistant bacteria among patients receiving care in high risk units in a Canadian tertiary care centre. DESIGN: Prevalence study over a four-month period in 1995 with rectal swab or freshly passed stool specimen collected from each patient included in study. Standardized record data extraction for selected patient variables was used. SETTING: Units at high risk for antimicrobial-resistant organisms at the Health Sciences Centre, Winnipeg, including neonatal (NICU), pediatric (PICU), surgical (SICU) and medical intensive care units (MICU), central dialysis unit (CDU), and the in-patient oncology ward (ONC). PATIENTS: One hundred and fifty-seven patients admitted to the high risk care units for at least 72 h were screened. Ward distribution was NICU 13 (8.3%), PICU nine (5.7%), SICU 24 (15.3%), MICU 19 (12.1%), CDU 62 (39.5%) and ONC 30 (19.1%). Fifty-one of 157 (32.5%) patients had urinary drainage devices, 108 (68.8%) had invasive vascular devices, and 57 (36.3%) had had a surgical procedure within the month before specimen collection. In the month before sampling, 114 (72.6%) had received antimicrobial therapy, including 21 (13.3%) who had received vancomycin, and 81 (51.5%) were receiving antimicrobials, seven (10.8%) vancomycin, on the day of sampling. RESULTS: Antimicrobial susceptibilities were performed on 371 bacterial isolates. There were no vancomycin-resistant enterococci or methicillin-resistant Staphylococcus aureus . Eleven (10.8%) enterococci were resistant to ampicillin, none of which were β-lactamase producers, 19 (18.6%) and five (4.9%) demonstrated high level resistance to gentamicin and streptomycin, respectively. One (0.7%) Escherichia coli was resistant to ciprofloxacin and another to gentamicin. Six (20.7%) Enterobacter cloacae samples were resistant to cefotaxime. One (2.4%) Klebsiella species was resistant to ciprofloxacin and another to cefotaxime. Two (16.6%) Citrobacter species were resistant to cefotaxime. One of 11 (9%) Pseudomonas aeruginosa isolates was resistant to ceftazidime; none were resistant to piperacillin, aminoglycosides, ciprofloxacin or imipenem. CONCLUSIONS: The prevalence of antimicrobial-resistant organisms colonizing the gastrointestinal tract in patients in these high risk units is low. The reasons for this low prevalence of antimicrobial resistance require further exploration.